The Influence of Economic Patronage on Interfaith Relations in Pusong Lama, Lhokseumawe - Rahmatul Ulya (Green Publisher Indonesia, 2026)
Indonesia faces increasing cases of intolerance despite its tradition of religious diversity. While cities in Aceh consistently rank low on the Tolerant City Index, Pusong Lama Village demonstrates successful management of religious tolerance. This study aims to explore how the people of Pusong Lama understand and practice tolerance in daily social activities and identify the social and institutional factors maintaining harmonious relationships. This research used a phenomenological approach to reveal the deep meaning and essential characteristics of life experiences related to religious tolerance. The subjects of the study are the head of Pusong Lama village, the youth leader, the chairman of the Tirta Lhokseumawe Buddhist Temple, FKUB, and several Muslim and non-Muslim Pusong residents. The data analysis techniques used are inductive/qualitative, data obtained through observation, interviews, and documentation. The results of the study show that religious diversity in Pusong Lama Village used to have a port and became a center of trade. The influx of immigrants from various religions and regions has caused a variety of religious umar Pusong Village has several houses of worship, namely the Batak Protestant Christian Huria Church (HKBP), the Indonesian Methodist Church (GMI), the Tirta Buddha Lhokseumawe Buddhist Temple, and the Al-Azhar Pusong Mosque. The Socio-religious relations are manifested in religious holiday celebrations, child adoption, orphan donations, social services, disaster response, and patron-client relationships, particularly trade patronage between ethnic Chinese (Buddhist and Christian) patrons and Acehnese Muslim clients.